2018
DOI: 10.1038/s41467-018-04211-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional heuristic process for high-yield production of astaxanthin and fragrance molecules in Escherichia coli

Abstract: Optimization of metabolic pathways consisting of large number of genes is challenging. Multivariate modular methods (MMMs) are currently available solutions, in which reduced regulatory complexities are achieved by grouping multiple genes into modules. However, these methods work well for balancing the inter-modules but not intra-modules. In addition, application of MMMs to the 15-step heterologous route of astaxanthin biosynthesis has met with limited success. Here, we expand the solution space of MMMs and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(169 citation statements)
references
References 52 publications
1
167
1
Order By: Relevance
“…Ajikumar et al [22] established a multivariate modular metabolic engineering (MMME) approach, which segments metabolic pathways into modules regulated by distinct promoters, to enhance taxadiene (a taxol intermediate) production by ~ 15,000 fold in E. coli. Variations of this modularization strategy have been implemented in E. coli [23,24] and in S. cerevisiae [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Ajikumar et al [22] established a multivariate modular metabolic engineering (MMME) approach, which segments metabolic pathways into modules regulated by distinct promoters, to enhance taxadiene (a taxol intermediate) production by ~ 15,000 fold in E. coli. Variations of this modularization strategy have been implemented in E. coli [23,24] and in S. cerevisiae [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they were able to achieve about 9.97 mg/g DCW of astaxanthin [70]. By developing and using an efficient multidimensional heuristic process and colorimetric medium screening approach, our laboratory has achieved one of the best results of astaxanthin using E. coli, 320 mg/L and 15 mg/g DCW [71]. As summarized in Table 2, the engineered S. cerevisiae [69], Y. lipolytica [66], Kluyveromyces marxianus [70] and E. coli [71] have produced promisingly high titers and yields of astaxanthin.…”
Section: Progress In Carotenoid Researchmentioning
confidence: 98%
“…Keasling's group tuned the expression of multiple genes within operons by generating libraries of tunable intergenic regions and balancing the expression of MVA pathway, which resulted in a 7-fold increase in mevalonate production (Pfleger et al, 2006). Zhang et al (2018b) reported a multidimensional heuristic process for astaxanthin production. Astaxanthin biosynthesis pathway was grouped into four modules, that each module controlled by different promoter of pre-determined strength, and get a yield of 320 mg/L in E. coli.…”
Section: Genetic Circuits and Dynamic Controlmentioning
confidence: 99%